Using non-invasive transcranial direct current stimulation for neglect and associated attentional deficits following stroke. Issue 5 (28th May 2022) - Olgiati, Elena; Malhotra, Paresh A.
ABSTRACT: Neglect is a disabling neuropsychological syndrome that is frequently observed following right-hemispheric stroke. Affected individuals often present with multiple attentional deficits, ranging from reduced orienting towards contralesional space to a generalized impairment in maintaining attention over time. Although a degree of spontaneous recovery occurs in most patients, in some individuals this condition can be treatment-resistant with prominent ongoing non-spatial deficits. Further, there is a large inter-individual variability in response to different therapeutic approaches. Given its potential to alter neuronal excitability and affect neuroplasticity, non-invasive brain stimulation is a promising tool that could potentially be utilized to facilitate recovery. However, there are many outstanding questions regarding its implementation in this heterogeneous patient group. Here we provide a critical overview of the available evidence on the use of non-invasive electrical brain stimulation, focussing on transcranial direct current stimulation (tDCS), to improve neglect and associated attentional deficits after right-hemispheric stroke. At present, there is insufficient robust evidence supporting the clinical use of tDCS to alleviate symptoms of neglect. Future research would benefit from careful study design, enhanced precision of electrical montages, multi-modal approaches exploring predictors of response, tailored dose-control applications and increased efforts to evaluate standalone tDCS versus its incorporation into combination therapy.